Europe from Below Notions of Europe and the European among Participants in EU Cultural Initiatives - Lähdesmäki, Tuuli (European Studies, 2021)
In this book, Tuuli Lähdesmäki, Katja Mäkinen, Viktorija L. A. Čeginskas, and Sigrid Kaasik-Krogerus scrutinize how people who participate in cultural initiatives funded and governed by the European Union understand the idea of Europe. The book focuses on three cultural initiatives: the European Capital of Culture, the European Heritage Label, and a European Citizen Campus project funded through the Creative Europe programme. These initiatives are examined through field studies conducted in 12 countries between 2010 and 2018. The authors describe their approach as 'ethnography of Europeanization' and conceptualize the attempts at Europeanization in the European Union's cultural policy as politics of belonging. Readership: Students, scholars, cultural policy administrators, cultural managers, heritage practitioners, and policy-makers interested in EU cultural and heritage policy and their implementation at the local level.